2014
DOI: 10.2528/pier14080503
|View full text |Cite
|
Sign up to set email alerts
|

Time-Domain Microwave Radar Applied to Breast Imaging: Measurement Reliability in a Clinical Setting

Abstract: Abstract-This work presents an evaluation of the measurement challenges in clinical testing of our microwave breast cancer screening system. The time-domain radar system contains a multistatic 16-antenna hemi-spherical array operating in the 2-4 GHz frequency range. We investigate, for the first time with such a system in clinical trials, the repeatability of measurements and its effect on image reconstruction. We record vertical and horizontal measurement uncertainties under different scenarios and verify usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Let us recall some early biomedical experiments that yielded two-dimensional (2D) transmission coefficient images [4] and 2D diffraction tomography (DT) images [5] of ex-vivo animal kidneys as well as 2D-DT images of an in-vivo human forearm [6]. Qualitative approaches also have been proposed, more recently, for breast cancer imaging, including ultra-wideband synthetic focusing techniques [7][8][9] and a linear sampling technique [10]. Since the nineties quantitative reconstruction algorithms based on rigorous solutions of Maxwell's equations have been developed to provide images of the complex permittivity profile, see, e.g., [11][12][13][14][15][16] for 2D and [13,[16][17][18][19] for 3D frequency-domain techniques and [20][21][22] for time-domain (TD) techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Let us recall some early biomedical experiments that yielded two-dimensional (2D) transmission coefficient images [4] and 2D diffraction tomography (DT) images [5] of ex-vivo animal kidneys as well as 2D-DT images of an in-vivo human forearm [6]. Qualitative approaches also have been proposed, more recently, for breast cancer imaging, including ultra-wideband synthetic focusing techniques [7][8][9] and a linear sampling technique [10]. Since the nineties quantitative reconstruction algorithms based on rigorous solutions of Maxwell's equations have been developed to provide images of the complex permittivity profile, see, e.g., [11][12][13][14][15][16] for 2D and [13,[16][17][18][19] for 3D frequency-domain techniques and [20][21][22] for time-domain (TD) techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave systems have been the focus of recent investigation, specifically as an alternative to mammography, because they offer several benefits: 1) there is no need for uncomfortable breast compression; 2) there is no use of potentially harmful ionizing radiation [4]; and 3) they have the potential to be more cost effective [5]. The body of research on microwave systems [5]- [9], including numerous clinical studies [10]- [13], has demonstrated that microwave methods are a promising and viable alternative to classic mammography.…”
Section: Introductionmentioning
confidence: 99%
“…Other groups, including our own, have opted for a TD system [7], [13], [14], in which short-duration broadband pulses are generated and used to illuminate the breast. The scattered signals are recorded (usually these are bistatic or multistatic signals as the switching time required for a monostatic system in the TD is a limiting factor) with an oscilloscope.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Electromagnetic (EM) waves in the microwave frequency band are non-ionizing and have tissue-penetrating abilities, making them highly suitable for diagnostic applications. Microwave imaging has been studied in both breast cancer detection [1], [2] and stroke imaging [3]- [5]. A recent attempt to detect bleeding stroke using microwave imaging has shown that EM waves in the 857-1670 MHz band transmit through the head and can be used to detect a volume of blood in the brain [5].…”
Section: Introductionmentioning
confidence: 99%